1996
DOI: 10.1093/mutage/11.3.221
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of the herbicides alachlor and maleic hydrazide in cultured human lymphocytes

Abstract: The herbicides alachlor and maleic hydrazide were evaluated for genotoxicity in peripheral blood human lymphocyte cultures. Sister-chromatid exchanges (SCE), chromosome aberrations (CA) and micronuclei (MN) were scored as genetic endpoints. To detect possible metabolic modifications in the genotoxicity of both herbicides, the cultures for SCE and MN demonstration were also treated with S9 fraction. From our results we conclude that, in the absence of metabolic activation, the two herbicides induce significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 7 publications
1
24
0
Order By: Relevance
“…Nevertheless, this frequency decreased drastically in the balancer heterozygous wings, indicating that this herbicide mainly induces mitotic recombination. These results confirm previous data from our group indicating that this chemical is genotoxic in Drosophila [Torres et al, 1992] and in human peripheral blood lymphocytes [Ribas et al, 1996]. In addition, maleic hydrazide has been reported as an efficient genotoxic agent in plants [Swietlinska and Zuk, 1978;Xiao and Ichikawa, 1995] but conflicting results were obtained in animal cells [Meschini et al, 1988].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, this frequency decreased drastically in the balancer heterozygous wings, indicating that this herbicide mainly induces mitotic recombination. These results confirm previous data from our group indicating that this chemical is genotoxic in Drosophila [Torres et al, 1992] and in human peripheral blood lymphocytes [Ribas et al, 1996]. In addition, maleic hydrazide has been reported as an efficient genotoxic agent in plants [Swietlinska and Zuk, 1978;Xiao and Ichikawa, 1995] but conflicting results were obtained in animal cells [Meschini et al, 1988].…”
Section: Resultssupporting
confidence: 91%
“…In this context, our findings, which show that in the HB cross the frequency of mutant clones is clearly reduced with respect to the response obtained in the ST cross, are of interest, because they support the hypothesis that the genotoxicity of maleic hydrazide is mediated by its biotransformation. In fact, in cultured human lymphocytes it has been shown that the addition of S9 reduced the frequency of sister-chromatid exchanges [Ribas et al, 1996].…”
Section: Resultsmentioning
confidence: 99%
“…Pesticides tend to be very reactive compounds that can form covalent bonds with various nucleophilic centers of cellular biomolecules, including DNA (Crosby, 1982). For instance, the induction of DNA damage can potentially lead to adverse reproductive outcomes, the induction of cancer and many other chronic diseases (Ribas et al, 1996;Lander et al, 2000;Meinert et al, 2000;Ji et al, 2001). A great variety of tests and test systems based on microbes, plant and animals have been developed in order to asses the genotoxic effects of xenobiotic agents, including pesticides.…”
Section: Cytogenetic Methods For Detection Of Pesticide Genotoxicitymentioning
confidence: 99%
“…In Germany, however, its use is not permitted. The use of MH in foodstuffs has been questioned as studies have shown links between MH and the production of tumours in mammals (Ribas et al 1996). It has been estimated that the average adult ingests approximately 630 mg of MH a day from potatoes, onions and tobacco from cigarette smoke (USEPA 1999).…”
Section: Maleic Hydrazidementioning
confidence: 99%